Perlindungan Hukum bagi Pemegang Hak Merek dikaitkan dengan Prinsip Itikad Baik dalam Proses Pendaftaran Merek - Fahmi Anugraha (CERED Indonesia, 2020)
Counterfeiting of the brand of a product or service often occurs in Indonesia. Almost the same brand for the same product often creates legal problems. The proliferation of well-known foreign products in Indonesia, provides a new homework for Indonesia, especially related to legal protection for these brands from counterfeiting that could occur. Business competition that is increasing both at home and abroad in the current era of global trade, makes the role of Intellectual Property Rights (IPR) law very important, especially in maintaining healthy business competition and to prevent the possibility of fraudulent competition in the form of imitation, piracy, as well as the use of Intellectual Property Rights without the rights of the real owner. This research uses the normative juridical method, which examines the formulation of legal protection issues in the trademark registration process in relation to the principles of good faith, and the responsibility of the Government is linked to the principle of good faith in the process of mark registration.